Karakteristik Interaksi Sosial pada Individu dengan Tipe Kepribadian Sanguinis: Studi Kualitatif - Yovan Bharagita Pratama; Sri Nurhayati Selian (FKIP UNSULTRA, 2026)
This study aimed to identify and describe the characteristics of social interactions among individuals with sanguine personality types. A qualitative approach with a descriptive design was employed. Three research subjects were selected through purposive sampling based on sanguine personality criteria. Data were collected through in-depth interviews, observation, and documentation, then analyzed using the Miles and Huberman model comprising data reduction, data display, and conclusion drawing with validity ensured through source and technique triangulation. The findings indicate that sanguine individuals exhibit communicative, expressive, sociable, and adaptive characteristics in social interactions. They demonstrate strong abilities in initiating conversations, building new relationships, and sustaining meaningful social bonds, alongside effective emotional management skills. However, tendencies toward unstructured communication and trivial conversations were also noted. Personality, family environment, and peer circles were identified as key influencing factors. This study contributes a nuanced, empirically grounded portrait of sanguine social interaction patterns, offering a novel qualitative perspective that enriches personality-based approaches in social psychology research.